Perceived usefulness, perceived ease of use, perceived enjoyment on behavioral intention to use through trust - Maria, Vita; Sugiyanto, Liem Bambang (Indonesian Journal of Multidisciplinary Science, 2023)
The purpose of this study was to find out how perceived usefulness, perceived ease of use, perceived enjoyment, and trust affect the behavioral intention to use shopeepay users in DKI Jakarta. This research is quantitative. The survey was conducted on 160 respondents who are or have used shopeepay. Data analysis was carried out using structural equation modeling with AMOS. The results show that perceived usefulness, perceived ease of use, and trust variables have a significant positive influence on behavioral intention. However, this is different from perceived enjoyment which has a positive and insignificant influence on behavioral intention to use. This is different from perceived usefulness, perceived ease of use, and perceived enjoyment which show insignificant results if mediated by trust. Research reveals that overall trust makes the greatest contribution to behavioral intention to use, followed by perceived ease of use and perceived usefulness. So the conclusion is that companies can increase behavioral intention to use through personal information data security which is the largest contributor indicator to personal information security from hacking. The limitations in the research, among others, the limited theoretical studies up to the time of data collection, the location and research objects which only focused on e-wallet users in the DKI Jakarta area, and the number of respondents who had not reached the maximum limit that should have been.